2015
DOI: 10.1049/iet-gtd.2014.0529
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and control of capacitor‐excited induction generators connected to a micro‐grid through power electronic converters

Abstract: A system consisting of a capacitor-excited induction generator (CEIG) with associated power electronic converters has been developed for supplying power to a micro-grid. The power fed to the grid from the CEIG is controlled using a diode bridge rectifier (DBR) and a pulse width modulated (PWM) inverter, connected between the generator terminals and the grid. A simple analog based hysteresis current control (HCC) technique has been employed in which the current control of the PWM inverter alone needs to be carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Self-excited induction generators have been widely used in renewable energy systems, such as wind power generation [1][2][3][4][5], as well as in isolated power systems, such as ships, aircrafts, and drilling platforms [6][7][8][9], due to their advantages of simplicity, robustness, low-cost, high reliability, no external excitation, and convenient maintenance. With rapid development of renewable and stand-alone energy generation systems, a lot of research has been carried out relating to self-excited induction generators.…”
Section: Introductionmentioning
confidence: 99%
“…Self-excited induction generators have been widely used in renewable energy systems, such as wind power generation [1][2][3][4][5], as well as in isolated power systems, such as ships, aircrafts, and drilling platforms [6][7][8][9], due to their advantages of simplicity, robustness, low-cost, high reliability, no external excitation, and convenient maintenance. With rapid development of renewable and stand-alone energy generation systems, a lot of research has been carried out relating to self-excited induction generators.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Rakesh et al [20] have made an elaborate survey of the major methods of performance analysis of SEIGs and concluded that making use of the genetic algorithm (GA) tool box in MATLAB software for the analysis of SEIG is very straightforward and simple compared to all other methods. This algorithm has been used in the recent years for the analysis of SEIGs [21–24], but only single machine systems have been considered, which involve only three unknown quantities ( X m , R m , and a ). Prior to the advent of GA, the net loop impedance of the equivalent circuit (Z loop ) of the single machine was equated to zero and then through lengthy derivations, the unknown quantities were evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the advent of GA, the net loop impedance of the equivalent circuit (Z loop ) of the single machine was equated to zero and then through lengthy derivations, the unknown quantities were evaluated. Compared to such complexities, the GA method is much simpler and its merits have been fully explained in [22–24]. In this context, it is felt that this GA technique will be even more adaptable for parallel operated SEIG systems which involve many more unknown parameters, namely, the magnetising reactances, core loss resistances of the generators and those of the inductor motor loads (Xmm,thickmathspaceRmm,,Xmg,thickmathspaceRmg), and the common operating frequency, a .…”
Section: Introductionmentioning
confidence: 99%
“…These SEIGs are used for feeding power to isolated loads, through suitable power electronic converters [4–10]. Suitably designed power electronic interfaces are also configured with SEIGs for maximum power point tracking for supplying micro‐grids [11–14]. Estimation of excitation capacitor, algorithms for arriving at optimised designs of SEIGs for meeting the required performance constraints and also changing the stator winding connections from delta to star for operating the SEIGs over extended rotor speeds have also been described in the literature [15–17].…”
Section: Introductionmentioning
confidence: 99%